Lectotypification of two names belonging to Olyra (Olyreae, Bambusoideae, Poaceae) - Oliveira, Iasmin Laiane De Castro; Dórea, Marcos Da Costa; Clark, Lynn G.; Oliveira, Reyjane Patricia De (Phytotaxa, 2021)
Olyra Linnaeus (1759: 238) is the best known genus of the herbaceous bamboos, belonging to the tribe Olyreae Kunth ex Spenner (1825: 172), which is composed of the subtribes Buergersiochloinae L.G.Clark & Judz. in Judziewicz & Clark (2007: 311), Parianinae Hackel (1887: 88) and Olyrinae Krombach (1875: 496) (Oliveira et al. 2014, Clark & Oliveira 2018, Ferreira et al. 2019, Oliveira et al. 2020a, Oliveira et al. 2020b). Olyra is the largest genus within the subtribe Olyrinae, including 25 species in its current delimitation, but this estimate will soon be revised since phylogenetic studies evidenced its non-monophyletic nature (Oliveira et al. 2014, Clark & Oliveira 2018, Oliveira et al. 2020a, Oliveira et al. 2020b). All species occur throughout the Neotropics, except O. latifolia Linnaeus (1759: 1261), which is also found in Africa/Madagascar and Sri Lanka (Judziewicz & Clark 2007, Ruiz-Sanchez et al. 2019).